Optimal Control Strategies for Operation of Hybrid Multi-Prime-Mover Ship Propulsion Powertrains in Transient Conditions - Topaloglou, Sotirios (Σχολή Ναυπηγών Μηχανολόγων Μηχανικών, 2016)
The prime movers used for ships today have certain limitations in their load response. As a ship accelerates, the diesel engine due to the temporary inability of the turbocharger to supply a sufficient amount of air to burn completely the fuel quantity required to meet the increasing load, emits smoke. One way of addressing this issue is the use of a hybrid diesel-electric configuration. Examples of ships with where a hybrid system could be useful, are vessels with fast maneuvering requirements with rapidly changing propeller demand. This Thesis investigates the improvement in performance of a combustion engine with the assistance of an electric motor, with appropriate control systems, for transient load uptake, smoke emission reduction, reduced pollutant emissions and lower fuel consumption. The Hybrid Integrated Propulsion POwertrain (HIPPO-1) test bed at NTUA/LME consists of a medium-duty 448 kW, turbocharged marine diesel engine, a water brake and an AC electric motor with frequency inverter rated at 110 kW, coupled to a water brake on the same shaft in a parallel hybrid configuration. The main purpose of the electric motor in the HIPPO-1 powertrain is to assist the diesel engine at lower speed bands, where the engine produces low torque, to meet faster the increasing torque demand. For the hybrid diesel electric powertrain, two energy control management strategies are proposed, that dictate the required torque from the electric motor so as to track a reference air-to-fuel ratio/stoichiometric ( lambda value) in the diesel engine. The reference lambda values are stored in lookup tables which consider engine parameters, such as produced torque, speed and intake manifold pressure, derived from experimental data during steady-state operation. The feasibility and validity of the proposed control strategy was tested experimentally, using rapid prototyping development tools. The tested loading time series is based on performance data from ship-board measurements with a multitude of engine loading conditions. A comparison between the hybrid powertrain and the standard engine setup (without the assistance from the electric motor), shows the benefits of a hybrid setup during transient loading conditions.